Pertanggungjawaban Pidana Jasa Pinjaman Online yang Menimbulkan Tindak Pidana terhadap Konsumen Pinjaman Online - Syerin Aurellia; Zulfikar Jayakusuma; Sukamarriko Andrikasmi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Online Lending Services are regulated by The Financial Services Authority(OJK) Number 77/POJK/01/2016 concerning Information Technology-BasedBorrowing and Borrowing Services. When a customer makes an online loantransaction, the desk collector will fill out the customer’s debt. However not a fewof these desk collectors cause criminal acts for their customers, many of theircustomers are constantly threatened by desk collectors so they feel threatened andare afraid of the threats from the desk collectors. Regarding criminal liability, it isoften limited to being borne by third parties. The main issues in this research are:How is law enforcement against Online Loan Services causing criminal actsagainst consumers of online loans; How is the criminal liability of online loanservices that causes criminal acts against consumers of online loans.The type of research used in this research is normative legal research or itcan also be called doctrinal legal research. Normative legal research is library lawresearch. This research is focused on legal principles. The principle of law used inthis research is the principle of expediency. The data analysis used in this researchis qualitative data analysis which will produce descriptive data.From the study results, it was concluded that, first, based on the legalanalysis conducted, law enforcement has not been fully applied to online loanservices as corporations. This is marked by the burden of criminal liability whichis only borne by third parties when it should have been the online loan services whowill take responsibility However, law enforcement is still minimal, even thoughArticle 53 paragraph (1) of the Financial Services Authority Regulation Number1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sectorhas directed this matter. Second, criminal liability so far has only focused on thirdparties, while online loan services as business entities are not subject to criminalliability. This is because regulations regarding online loan arrangements havelimitations in terms of specific rules (lex specialis) which result in online loanservice businesses still being able to operate even though the desk collector hascommitted a crime and has been given a sanction.Keywords: Criminal Liability – Online Loans – Criminal Acts - Consumers